2018
DOI: 10.17221/359/2018-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biochar on sodium ion accumulation, yield and quality of rice in saline-sodic soil of the west of Songnen plain, northeast China

Abstract: This study evaluated the effects of biochar application on sodium ion accumulation, yield and quality of rice in saline-sodic soil by using a pot experiment. Rice was grown in the soil with no biochar, 15 g biochar per kilogram soil, 30 g biochar per kilogram soil and 45 g biochar per kilogram soil. The results indicated that biochar application significantly decreased sodium ion accumulation of rice plant parts, while it obviously increased rice dry biomass, grain yield and improved rice quality. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…BC at 2% improved wheat growth and increased its height by 11% (Kanwal et al, 2018), while 5 % BC under salinity improved soil fertility and increased sorghum biomass yield by 25 % (Edmunds, 2012). In addition, 1.5, 3.0 and 4.5 % BC in saline-sodic paddy soil reduced stress and promoted rice yield (Jin et al, 2018), while BC improved the legume yield in the calcareous soil in arid area (Azeem et al, 2016). Diatta (2016) reported that 20 tons BC/ha could improve soil fertility and crop productivity in temperate soils but had limited effects on sandy, salt-stressed soils may be due to differences in soil properties.…”
Section: Introductionmentioning
confidence: 99%
“…BC at 2% improved wheat growth and increased its height by 11% (Kanwal et al, 2018), while 5 % BC under salinity improved soil fertility and increased sorghum biomass yield by 25 % (Edmunds, 2012). In addition, 1.5, 3.0 and 4.5 % BC in saline-sodic paddy soil reduced stress and promoted rice yield (Jin et al, 2018), while BC improved the legume yield in the calcareous soil in arid area (Azeem et al, 2016). Diatta (2016) reported that 20 tons BC/ha could improve soil fertility and crop productivity in temperate soils but had limited effects on sandy, salt-stressed soils may be due to differences in soil properties.…”
Section: Introductionmentioning
confidence: 99%
“…Rice ( Oryza sativa L.), an important food crop worldwide, is used as a desalinization crop in saline‐alkaline soils (Lv et al., 2013). During rice cultivation, the ground is submerged for a long period, and the water washes salts from the soil, gradually reducing the concentration of salts and improving the soil (Jin et al., 2018; Safi‐naz, 2016). Therefore, planting rice in sodic soils not only improves soil salinity but also increases rice yield, which is important for food security.…”
Section: Introductionmentioning
confidence: 99%
“…The authors' experiments also consistently found that under saline-sodic paddy soil, K + and K + /Na + ratio in rice root system was increased significantly (Fig. 2), thus improving cell membrane integrity, increasing water potential, and enhancing salinity tolerance and growth of rice (Jin et al 2018;Ran et al 2020). Yue et al (2016) also found that biochar application could accelerate salt leaching, lower soil EC, and provide a good environment for growth and development of plant roots.…”
Section: Effect Of Biochar On the Ionic Accumulation And Root Physiol...mentioning
confidence: 68%